Wireless, smart hemostasis device with all-soft sensing system for quantitative and real-time pressure evaluation - Zhang, Chengjun (2023)
The properly applied pressure between the skin and hemostasis devices is an essential parameter for preventing bleeding and postoperative complications after a transradial procedure. However, this parameter is usually controlled based on the subjective judgment of doctors, which might cause insufficient hemostatic effect or thrombosis. Here this study develops a compact and wireless sensing system for continuously monitoring the pressure applied on the radial artery and wrist skin in clinical practice. A liquid metal (LM)-based all-soft pressure sensor is fabricated to enable conformal attachment between the device and skin even under large deformation conditions. The linear sensitivity of 0.007 kPa-1 among the wide pressure range of 0-100 kPa is achieved and the real-time detection data can be wirelessly transmitted to mobile clients as a reference pressure value. With these devices, detailed pressure data can be collected, analyzed, and stored for medical assistance as well as to improve surgery quality.